The remote sensing data book - Rees, Gareth, 1959- (Cambridge University Press, 1999)
The Remote Sensing Data Book is a unique resource of information for the expert and non-expert alike. It contains over 700 alphabetically-arranged and cross-referenced entries on how remote sensing works, what kinds of data are available, and the large number of satellites and instruments from which information is obtained.